2020
DOI: 10.3390/molecules25235600
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Compositions of Essential Oils Derived from Cryptocarya alba and Laurelia sempervirens Possess Antioxidant, Antibacterial and Antitumoral Activity Potential

Abstract: Cryptocarya alba (Peumo; CA) and Laurelia sempervirens (Laurel; LS) are herbs native to the Chilean highlands and have historically been used for medicinal purposes by the Huilliches people. In this work, the essential oils were extracted using hydrodistillation in Clevenger apparatus and analyzed by GC-MS to determine their composition. The antioxidant capacity (AC) was evaluated in vitro. The cytotoxicity was determined using cell line cultures both non tumoral and tumoral. The toxicity was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
0
21
1
2
Order By: Relevance
“…In this context, the variability in the essential oil content is influenced by the Some studies of leaf EOs from L. sempervirens showed different chemical compositions according to the region. The results of this work show that the chemical composition of this EO was different with those obtained from plants collected in the Metropolitan, Ñuble, Bio-Bío and La Araucanía regions [14,16,17,22]. The most important differences are found in the absence of spatulenol content, the lower isosafrole content, and a higher safrole content.…”
Section: Yield and Chemical Constituents Of Eocontrasting
confidence: 57%
See 1 more Smart Citation
“…In this context, the variability in the essential oil content is influenced by the Some studies of leaf EOs from L. sempervirens showed different chemical compositions according to the region. The results of this work show that the chemical composition of this EO was different with those obtained from plants collected in the Metropolitan, Ñuble, Bio-Bío and La Araucanía regions [14,16,17,22]. The most important differences are found in the absence of spatulenol content, the lower isosafrole content, and a higher safrole content.…”
Section: Yield and Chemical Constituents Of Eocontrasting
confidence: 57%
“…is an evergreen endemic tree of the temperate rainforests of southern Chile [13]. Numerous pharmacological and phytochemical studies have reported repellent, insecticidal, antibacterial, antioxidant, antitumoral and antifungal activity potential of essential oil from L. sempervirens [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the antimicrobial potential of camphene demonstrated a broad spectrum but variable activity of this compound, depending on the strain and technique used for antimicrobial testing [25] . Limonene was previously reported to possess moderate to strong antimicrobial activity, [26–28] but it was also determined that this activity may be enhanced by acting synergistically with other compounds, so in mixtures such as EOs the activity of both limonene and accompanying compounds is higher [29] . In the case of the herein tested EOs, we cannot relate the activity of the EOs to presence of these two compounds.…”
Section: Resultsmentioning
confidence: 77%
“…The fruit is edible (cooked or fresh), and the aromatic leaves can be used as a facial mask to clean the skin [ 33 ]. In addition, the EOs of this specie seem to have antioxidant and antibacterial properties [ 45 ].…”
Section: Antimicrobial Properties Of Chilean Native Plantsmentioning
confidence: 99%